Effect of supercritical carbon dioxide on tensile Properties of Durian skin fibre biocomposite - Mohd Apandi, Siti Nur E’zzati; Anuar, Hazleen; Abd. Rashid, Siti Munirah Salimah; Buys, Yose Fachmi; Othman, Rashidi (UR Publishers, 2018)
The exploration of new biocomposites that are environmental friendly is gain attention due to depletion of petroleum resources and increasing global environmental concern. Therefore, the investigation of environmental friendly and sustainable materials requires to substitute the synthetic based materials. This project is conducted to investigate the effect of supercritical carbon dioxide on tensile properties of PLA/DSF biocomposite films. The PLA/DSF biocomposites are produced via solvent casting method. Then, the samples are treated under supercritical carbon dioxide (SCCO2) at 40oC and at 200 bar pressure. From tensile properties, it was found that the tensile strength and modulus for untreated and treated PLA/DSF biocomposite are higher compared to net PLA which are 24.9 MPa and 23.5 MPa. Thus, the addition of durian skin fiber improved the mechanical strength PLA polymer. But, the presence of foams and pore in treated PLA/DSF biocomposites decreased its tensile properties by 1.4 MPa less compared to untreated samples as confirmed by morphological observations under scanning electron microscope.